2004
DOI: 10.1128/mcb.24.16.6907-6918.2004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochores Prevent Repair of UV Damage in Saccharomyces cerevisiae Centromeres

Abstract: Centromeres form specialized chromatin structures termed kinetochores which are required for accurate segregation of chromosomes. DNA lesions might disrupt protein-DNA interactions, thereby compromising segregation and genome stability. We show that yeast centromeres are heavily resistant to removal of UVinduced DNA lesions by two different repair systems, photolyase and nucleotide excision repair. Repair resistance persists in G 1 -and G 2 /M-arrested cells. Efficient repair was obtained only by disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…No repair was detected in the centromere of chromosome XIV, whereas the centromere flanking regions were efficiently repaired (Figure 2). This supports our previous results that showed a strong inhibition of photoreactivation and nucleotide excision repair by kinetochore proteins (Capiaghi et al , 2004).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…No repair was detected in the centromere of chromosome XIV, whereas the centromere flanking regions were efficiently repaired (Figure 2). This supports our previous results that showed a strong inhibition of photoreactivation and nucleotide excision repair by kinetochore proteins (Capiaghi et al , 2004).…”
Section: Resultssupporting
confidence: 93%
“…CPDs were mapped by indirect end labeling and quantified as described (Suter et al , 1997; Capiaghi et al , 2004). This method allows correlating CPD distribution with positioned nucleosomes, linker DNA, and nuclease‐sensitive regions (compare Figures 1, 2 and 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the histone acetylation level (histones H3 and H4) in the centromere sequence, CEN14. The CEN14 sequence is packed in a compact chromatin structure termed the kinetochore, where UV-induced DNA damage is heavily resistant to NER (26). The histone acetylation level at CEN14 was constant before and after UV irradiation and served as an internal control for the examination of the histone acetylation level at MFA2.…”
Section: Gcn5p Is Required For Efficient Ner Of Uv-induced Cpds In Thementioning
confidence: 99%
“…Already, Thoma has shown that NER is inefficient in certain sequences in the centromeric regions. 17 Some chromatin remodeling must occur in relation to DNA replication. Does repair of these regions come under the auspices of certain remodeling events related to replication and the cell cycle rather than transcription?…”
Section: Histone Acetylation Chromatin Remodeling and Nucleotide Excmentioning
confidence: 99%